A Mixed Method Study of Teachers' Appraisals of Student Wellness Services and Supports During COVID‐19. (5th April 2022) - Childs, Tasha M.; Brown, Elizabeth Levine; Brown, Naomi; Iachini, Aidyn L.; Phillippo, Kate; Galib, Linda; Parker, Audra; Fujimoto, Ken
ABSTRACT: BACKGROUND: Understanding teachers' appraisals of student wellness services and supports during COVID‐19 is essential to strengthening services and improving student health outcomes. This mixed‐method study aimed to examine US PK‐12 teachers' appraisals of student wellness services and supports during COVID‐19. METHODS: This study focuses on qualitative data from 291 teachers' open‐ended responses to the question: "What do you wish your school leaders knew about this (wellness support) aspect of your work?" and whose responses described wellness services and supports. A qualitative content analysis was conducted by an interdisciplinary research team using open‐ and axial coding. RESULTS: Three main themes emerged. (1) insufficient access to mental health professionals and programming at schools, (2) concern about the quality of available services, and (3) a need for teacher professional development and support on student wellness. Statistically significant differences in teacher appraisals of insufficient access to mental health professionals and programming were found based on grade level taught and percentage of immigrant students in the school. CONCLUSION: With amplified student wellness needs, school personnel, including school leaders, must consider ways to allocate additional resources/staffing, assess the quality of services and supports, and design professional development opportunities to support teachers' involvement in supporting student wellness needs.